Determination of Grafting Adaptation of Some Chestnut (Castanea sativa Mill.) Genotypes with Marigoule (C. Sativa × C. Crenata) Cultivar - Şemsettin Kulaç; Hatice Nihan Nayır (Turkish Journal of Agriculture: Food Science and Technology, 2021)
In this study, to reproduce natural chestnut genotypes, the fruit characteristics of the Düzce region determined by local people are good in a healthy way, compatible with Marigoule (C. sativa × C. crenata) hybrid varieties resistant to branch cancer and root rot was investigated. In this study, 24 different chestnut genotypes were used. As the grafting method, the most commonly used tongue grafting, split grafting, chip budding grafting, and side grafting method were used. All procedures related to grafting were carried out in the greenhouses of the Düzce University Faculty of Forestry. In this study, local genotypes that are compatible with Marigoule chestnut were determined. As a result, the native genotype, which showed the best adaptation to Marigoule seedlings, was 87.5% of Yalnızçam, and after that, 79.2% of the Ereğli Sefer genotype. The lowest fit showed Broken genotype with 15% and Akçakoca1genotype with 17.5%. Besides, the compatibility of foreign varieties Maraval, Marigoule, and Betizac were also investigated. As a result, Betizac had the highest compatibility with 95%, while Maraval had 67.5%. The most successful in the grafting methods applied was the side graft (74.2%) followed by tongue grafting (59.9%), splitting grafting (51.4%), and chip budding grafting (29.7%).